Online Learning During The COVID-19 Pandemic - Bustan Bustan (Universitas Negeri Makassar, 2024)
Learning during the COVID-19 pandemic has its own challenges for teachers. As a teacher, you are not only required to be an expert in delivering material or teaching materials offline (face to face in class), but you are also required to be able to use an online learning system with an attractive design. Some obstacles will certainly be found in the online learning process, so that good collaboration between teachers and students will be able to find solutions to the obstacles faced. This research is Classroom Action Research. Learning during the Covid-19 pandemic has become interesting to research to understand the effectiveness of learning. In detail we can describe the supporting and inhibiting factors in online learning. Likewise regarding the strategies teachers apply in conducting online learning for students. It is on this basis that prospective researchers have an interest in understanding more deeply about the learning system during the Covid-19 pandemic with a focus on Junior High Schools (SMA) in Barru Regency.